Failure Analysis of a Highway Cut Slope with Anti-Slide Piles - Hongjie Chen; Guangcheng Zhang; Zheng Chang; Lian Wen; Wentao Gao (Geofluids)
Landslides induced by engineering construction are very common in reality; it is necessary to clarify the causes of landslide failure to avoid similar accidents. A landslide induced by highway construction is taken as a case. Field observations, data collection, and analyses were used to investigate the deformation and causes of the landslide. The failed slope is mostly comprised of gravel soil, there were some shear cracks on both sides of the slope before sliding, and most tensile cracks were connected with shear cracks after sliding. The cut slope of this highway was designed to be protected by prestressed anchor sheet piles. However, in the construction process, the slope in front of the antipiles was removed when the piles were constructed without any anchor cables, which led to the shear damage of a row of anti-slide piles with a 15-meter-long cantilever. Moreover, continuous rainfall over several days aggravated the landslide damage because of increase of the self-weight and degradation of the mechanical parameters of the slope materials. The mechanical and simulation analyses both show that the resistance provided by the cantilever piles was not enough to prevent the force behind the piles. The irrational construction process and rainfall caused the slope failure.